Real-Time Based Big Data and E-Learning: A Survey and Open Research Issues - Wael Hadeed; Dhuha Abdullah (Al-Rafidain Journal of Computer Sciences and Mathematics)
Big data is considered a remarkable aspect of development communication and information systems. In terms of delivery, retrieval, and storage, a vast volume of complex data exceeds the capability of conventional software and device capabilities. As a result, advanced alternative solutions that allow their control flow is becoming more prevalent. One of the most difficult fields of information management and technology is the real-time management, analysis, and processing of big data. These issues can be seen in a large amount of everyday produced data in a variety of places, including online social networks and the method of logging cell phone data. This survey looks at several studies that use a range of methods to handle, interpret, and process big data in real-time. Hence, the objective of this survey is to provide a comprehensive overview of the integration between real-time and big data fields of study with the field of E-learning. Finally, this survey also presents the colorful aspects of big data and their relationship to E-learning domains such that e-learning platforms, big data frameworks, and datasets used.